Injectable hyaluronic acid hydrogels encapsulating drug nanocrystals for long‐term treatment of inflammatory arthritis. Issue 1 (15th September 2021) - Gao, Yongsheng; Vogus, Douglas; Zhao, Zongmin; He, Wei; Krishnan, Vinu; Kim, Jayoung; Shi, Yujie; Sarode, Apoorva; Ukidve, Anvay; Mitragotri, Samir
Abstract: Antiproliferative chemotherapeutic agents offer a potential effective treatment for inflammatory arthritis. However, their clinical application is limited by high systemic toxicity, low joint bioavailability as well as formulation challenges. Here, we report an intra‐articular drug delivery system combining hyaluronic acid hydrogels and drug nanocrystals to achieve localized and sustained delivery of an antiproliferative chemotherapeutic agent camptothecin for long‐term treatment of inflammatory arthritis. We synthesized a biocompatible, in situ‐forming injectable hyaluronic acid hydrogel using a naturally occurring click chemistry: cyanobenzothiazole/cysteine reaction, which is the last step reaction in synthesizing D ‐luciferin in fireflies. This hydrogel was used to encapsulate camptothecin nanocrystals (size of 160–560 nm) which released free camptothecin in a sustained manner for 4 weeks. In vivo studies confirmed that the hydrogel remained in the joint over 4 weeks. By using the collagen‐induced arthritis rat model, we demonstrate that the hydrogel‐camptothecin formulation could alleviate arthritis severity as indicated by the joint size and interleukin‐1β level in the harvested joints, as well as from histological and microcomputed tomography evaluation of joints. The hydrogel‐nanocrystal formulation strategy described here offers a potential solution for intra‐articular therapy for inflammatory arthritis.